When brute force fails: how to have less crime and less punishment - Kleiman, Mark (Princeton Univ. Press)
The trap -- Thinking about crime control -- Hope -- Tipping, dynamic concentration, and the logic of deterrence -- Crime despite punishment -- Designing enforcement strategies -- Crime control without punishment -- Guns and gun control -- Drug policy for crime control -- What could go wrong? -- An agenda for crime control